Positive reinforcement in probation practice: The practice and dilemmas of praise - Mullins, Eve (Probation journal, 2024)
Positive reinforcement is a key part of probation practice, and linked to client desistance from offending. The main way practitioners positively reinforce clients’ prosocial comments or behaviours is through praising them. However, praise is tricky in interaction, as people are under pressure to accept the positive assessment whilst also avoiding self-praise. Applying conversation analysis to 21 video recordings of probation sessions originally collected for the Jersey Supervision Skills Study, we examine how this important aspect of probation features and functions in practice, and how clients respond. Our analysis shows how practitioners and clients manage the practice and dilemmas of praise.